(untitled) (Research, Society and Development, 2019)
This article aims to discuss Professional Didactics, a French approach that emerged in the 1990s and is still less widespread in Brazil, presenting its structure, including the elements that may contribute to Professional Education in Brazil. as with the teacher training of the PE teacher. Therefore, a brief context is also made about professional education in Brazil, in order to signal the current situation of PE. The research has a bibliographical character and is focused on research on professional didactics. The result shows that in order to work as a teaching professional in Brazilian Professional Education there is still no specific training aimed at such modality. Therefore, the need for Professional Teaching in order to collaborate with teaching practice in the Federal Institutes of Education is concluded. in view of the need and opportunity of evolution in what concerns didactic in a general way, always seeking the transformation of individuals in their onilaterality, and integral human formation.